Microencapsulation of Vitamin A by spray-drying, using binary and ternary blends of gum arabic, starch and maltodextrin - Ribeiro, AM (2020)
Vitamin A is a bioactive compound responsible for many biological functions being, for that reason, extremely beneficial for the human organism. However, its sensitivity to certain adverse conditions as well as their insolubility in water, make infeasible their direct application into functional products. In this context, in the current work, vitamin A was encapsulated by spray-drying, using different blends of gum arabic, maltodextrin and starch, and the obtained particles evaluated in terms of controlled release. Particles with a size between 6.94 and 11.61 mu m were obtained, presenting a regular shape and a surface structure that depends on the encapsulating agent used. The release times were influenced by the wall material, being the starch samples associated to lower values of this variable and the maltodextrin particles the ones that lead to more sustained releases. The ternary blend presented an intermediate release time, due to the contribution of the three encapsulating agents. Different kinetic equations were adjusted to the release profiles, being the Weibull model the one that, simultaneously, presented good correlation coefficients (0.9009-0.9655) and adjusted to a great number of points. The product yield and encapsulation efficiency were also calculated, presenting values between 7-39% and 88-98%, respectively. In the end, viable particles were produced, regardless of the encapsulating agent used. However, the ternary blend was the wall material combination that led to particles with better encapsulation efficiencies and, at the same time, to particles that ensured a compromise between all the variables tested, presenting moderate values in terms of size, product yield and release times. For that reason, a ternary blend of gum arabic, maltodextrin and starch would be a wise choice for future formulations of functional products.